The politics of evidence-based policy: A comparative analysis of climate adaptation in Australia and the UK. (September 2016) - Tangney, Peter; Howes, Michael
This paper presents a comparative analysis of the use of climate science for adaptation policy in Queensland, Australia and the UK. We examine policy players' perceptions of climate science alongside prevailing political influences on evidence-based policy making. In Queensland, the evidence-based mandate has been weakened by partisan politics so that the political acceptability of evidence is a foremost concern for policy makers. In the UK, the evidence-based mandate is enshrined in the Climate Change Act (2008), yet here too political forces have sought to limit the acceptable use of climate science for policy making. Both cases reveal normative and political tensions in the interpretation and use of climate science, suggesting that important political challenges must be overcome by the scientific community to ensure the ongoing utility of climate science for policy making.